THE GENERAL METHODOLOGICAL PRINCIPLES OF COMBINED OPTIONAL ONLINE ENGLISH LANGUAGE TRAINING OF PRIMARY SCHOOL STUDENTS - E. I. Zadorozhnaya (Образование и наука)
The aim of the publication is to demonstrate the implementation of general methodological principles of optional elementary school online foreign languages learning on an example of a virtual course for students of the second and third grades.Methods. The methods involve pedagogical modeling and projecting; the experience of foreign and Russian methodists, teachers and researchers is analysed, generalized and adjusted to the modern realias.Results and scientific novelty. On the basis of the requirements of the state educational standard and interest of pupils in computer games, the author’s technique of the combined facultative educational activities integrated to training in English at elementary school is developed. Online training in the form of games (additional to the major classroom activities) gives a possibility of the choice of tasks interesting to children, studying the material at optimum comfortable and individual speed; it is possible to perform the tasks at home excluding the stressful situations that are specific to school examination, and allows pupils to master most effectively personal, metasubject and object competences. In general context of quality improvement of the general education, the modernization of educational process assumes not only justification of its new maintenance, but also restructuring of scientific and methodical support which has to meet essential needs of teachers and pupils, to facilitate access to necessary specific information. The lack of methodical base of creation of electronic distance resources for foreign-language education of younger school students has motivated the author to create own methodical concept of online training taking into account age of pupils. The complex of the general methodical principles is thoroughly considered; based on the general methodical principles, the proposed modular technique of the organization of an online class is created and implemented. Interactive blocks are described; these blocks are the component units of each module in the educational space of the educational portal LearningApps.org – technological base of an online course of a foreign language.Practical significance. The results of the diagnostic studies, showed in the article, suggest that the use of the proposed general methodological principles increase the percentage of the knowledge quality, promote the development of initial linguistic representations required to master at the elementary level of oral and written skills in a foreign language, enrich linguistic horizons of students. It contributes to the development of motivation to learn foreign Language, as well as the formation of such metasubject result as the ability to learn and plan their activities. Online environment gives the chance to synchronize the problem solution of providing the trainee with information and methodical material; facilitates search by a teacher of an optimum way of achievement of the practical pedagogical purposes. As a consequence of flexibility and usability of educational means on the LearningApps.org portal, the teacher can quickly change blocks and create additional ones according to the needs of pupils and new thesis. It gives the grounds for a conclusion about prospects of online courses accompanying the main educational programs and lessons at school.